The city in process - Cole, Ariane Daniela (Pós. Revista do Programa de Pós-Graduação em Arquitetura e Urbanismo da FAUUSP, 2007)
This article suggests bringing the artistic creation process closer to the construction of cities through art history, phenomenology of perception, and genetic criticism, which studies the artistic creation process. This approximation takes place both from the perspective of the construction and transformation of cities, as well as from that of interlocution and interaction between art and the city. Art history, phenomenology, and genetic criticism all observe the extent to which memory and imagination, together with perception, are essential elements of subjectivity and tools for creating reality; it is through perception that we observe the reality that becomes part of our being. According to the phenomenology of Merleau-Ponty (1969), the world is arranged from the original experience, at a pre-reflexive level, where the body is the threshold for dialogue between the world and the self. Thus, according to this author, form is not something outside the self; to have some kind of meaning, it is necessary to have some kind of communication between objectivity and subjectivity, since form is expressed out of something perceived and created. To this effect, perception, memory, and imagination are important agents in constructing reality itself, both individually and collectively. At the core of this analysis rises the interlocution between art and city and the importance of the visual as a manifestation of perception and expression. Genetic criticism is included by analyzing the phenomena that present themselves in the processes of artistic creation and the construction and transformation of cities, in the search for similarities, correspondences, and parallels. Thus, we will observe the complex movement of creation, where actions covering research, experimentation, chance, tests, the collection and storage of information, appropriations, and discarding, as well as transgressions, adjustments, digressions, and returns, all interact with each other.